CURABLE RESIN COMPOSITION FOR LOW DIELECTRIC CONSTANT MATERIAL, CURED PRODUCT OBTAINED FROM THE RESIN COMPOSITION, AND LOW DIELECTRIC CONSTANT MATERIAL

The curable resin composition, featuring structural units a and b, addresses the limitations of existing low-dielectric constant materials by achieving excellent film formation, low dielectric properties, and transparency in the cured product, along with enhanced heat resistance.

JP7665944B2Active Publication Date: 2025-04-22SUMITOMO BAKELITE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020163196
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-29
Publication Date
2025-04-22
Estimated Expiration
2040-09-29

AI Technical Summary

Technical Problem

Existing resin compositions for low-dielectric constant materials, such as those described in Patent Document 1, do not adequately achieve low dielectric properties and transparency.

Method used

A curable resin composition containing at least one structural unit a represented by general formula (1) and at least one structural unit b represented by general formula (2), which are specifically designed to enhance film formation properties and achieve excellent low dielectric properties and transparency in the cured product.

Benefits of technology

The curable resin composition effectively produces a cured product with excellent film formation properties, low dielectric properties, and transparency, while also offering improved heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665944000001
    Figure 0007665944000001
  • Figure 0007665944000002
    Figure 0007665944000002
  • Figure 0007665944000003
    Figure 0007665944000003
Patent Text Reader

Abstract

To provide a curable resin composition for a low dielectric constant material from which a cured product having excellent film-forming property, and low dielectric characteristics and transparency is obtained.SOLUTION: A curable resin composition for a low dielectric constant material contains a polymer containing at least one structural unit a represented by the following general formula (1), and at least one structural unit b represented by the following general formula (2).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable resin composition for a low dielectric constant material, a cured product obtained from the resin composition, and a low dielectric constant material. [Background technology]

[0002] Various developments have been made so far regarding cyclic olefin polymers. For example, the technology described in Patent Document 1 is known as this type of technology. Patent Document 1 describes the use of a resin composition obtained by kneading a cyclic olefin polymer having a glass transition temperature of 101 to 160°C with another elastomer as a molding material (Patent Document 1, claim 1, paragraph 0042, etc.). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2013-231171 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the resin composition described in Patent Document 1 above has room for improvement in terms of low dielectric properties. As a result of investigations, the present inventors have found that by appropriately selecting the structure of the structural units of a cyclic olefin polymer, it is possible to obtain excellent film-forming properties, and further, the obtained cured product has excellent low dielectric properties and transparency, and have thus completed the present invention. According to the present invention,

[0005] It is possible to provide a curable resin composition for low dielectric constant material, which contains a polymer including at least one type of structural unit a represented by the following general formula (1) and at least one type of structural unit b represented by the following general formula (2). [ka] In the general formula (1), m is 0, 1 or 2. In the general formula (2), X represents a linear or branched alkyl group having 3 to 20 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group. n is 0, 1, or 2.

[0006] According to the present invention, it is possible to provide a cured product obtained by curing the curable resin composition for a low dielectric constant material. According to the present invention, it is possible to provide a low dielectric constant material comprising the above-mentioned cured product. Effect of the Invention

[0007] According to the present invention, it is possible to provide a curable resin composition for low dielectric constant material, which has excellent film-forming properties and can give a cured product having low dielectric properties and excellent transparency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, the present invention will be described based on the embodiments. In addition, "~" indicates "above" to "below" unless otherwise specified. The curable resin composition for a low dielectric constant material (hereinafter, may be referred to as a curable resin composition) of this embodiment contains a polymer (A).

[0009] [Polymer (A)] The polymer (A) of the present embodiment contains at least one type of structural unit a represented by the following general formula (1) and at least one type of structural unit b represented by the following general formula (2).

[0010] [ka]

[0011] In the general formula (1), m is 0, 1 or 2, and preferably 0 or 1. In the general formula (2), X represents a linear or branched alkyl group having 3 to 20 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group, and is preferably a linear or branched alkyl group having 3 to 20 carbon atoms. A plurality of X present in the polymer (A) may be the same or different.

[0012] Examples of the linear or branched alkyl group having 3 to 20 carbon atoms include a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, a dodecyl group, a tetradecyl group, an octadecyl group, an isopropyl group, an isobutyl group, a sec-butyl group, a t-butyl group, a 1-ethylpentyl group, and a 2-ethylhexyl group.

[0013] Examples of the cycloalkyl group having 3 to 10 carbon atoms include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, etc. Examples of the polycyclic cyclic alkyl group include an adamantyl group, a norbornyl group, a bornyl group, a camphenyl group, a decahydronaphthyl group, a tricyclodecanyl group, a tetracyclodecanyl group, a campholoyl group, a dicyclohexyl group, and a pinenyl group.

[0014] Examples of the aryl group include a phenyl group, a naphthyl group, an anthracenyl group, a phenanthryl group, a pyrenyl group, a perylenyl group, a fluoranthenyl group, and the like. n is 0, 1 or 2, preferably 0 or 1.

[0015] The curable resin composition for low dielectric constant material of the present embodiment contains a polymer (A) containing at least one of the structural units a and at least one of the structural units b, and can be cured by light or heat, or a combination of light and heat, and can provide a cured product with excellent film-forming properties, low dielectric properties, and transparency. The cured product also has excellent heat resistance.

[0016] In this embodiment, from the viewpoint of the effects of the present invention, the polymer (A) may further contain at least one type of structural unit c represented by the following general formula (3).

[0017] [ka]

[0018] In general formula (3), R each independently represents an alkoxy group having 1 to 3 carbon atoms or an alkyl group having 1 to 3 carbon atoms, and at least two R are alkoxy groups having 1 to 3 carbon atoms. A plurality of R present in polymer (A) may be the same or different. p represents an integer of 0 to 3.

[0019] The alkoxy group having 1 to 3 carbon atoms is a methoxy group, an ethoxy group, and a propoxy group, and the alkyl group having 1 to 3 carbon atoms is a methyl group, an ethyl group, and a propyl group. l is 0, 1 or 2, preferably 0 or 1.

[0020] Since the curable resin composition of the present embodiment is used for a dielectric constant material, it is preferable that the polymer (A) does not contain a constitutional unit derived from maleic acid or maleimide. Furthermore, the polymer (A) does not contain any polar functional groups such as a carboxyl group, an epoxy group, an ester group, or an amino group.

[0021] In order to cure the polymer (A), it is preferable that the polymer (A) contains a structural unit derived from maleic acid or maleimide or contains a polar functional group in the structure, but the resulting cured product has an increased dielectric constant, so there is a trade-off between curability and low dielectric constant. The polymer (A) of this embodiment contains the structural unit a and the structural unit b, and optionally contains the structural unit c, and can obtain a cured product that does not contain a structural unit derived from maleic acid or maleimide or a polar functional group, and further, since it does not contain a polar functional group, the cured product has excellent low dielectric constant and excellent transparency.

[0022] From the viewpoint of the effect of the present invention, the lower limit of the content of the polymer (A) is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more, based on 100% by mass of the curable resin composition of the present embodiment. This can further improve the heat resistance of the resin material. On the other hand, the upper limit of the content of the polymer (A) may be, for example, preferably 100% by mass or less, more preferably 99% by mass or less, and even more preferably 95% by mass or less. This can achieve a balance of various properties.

[0023] The lower limit of the glass transition temperature (Tg) of the polymer (A) is, for example, 80° C. or higher, preferably 100° C. or higher, and more preferably 120° C. or higher. This can further improve the hot properties of the resin material. On the other hand, the upper limit of the glass transition temperature of the polymer (A) is not particularly limited, and may be, for example, 400° C. or lower, 350° C. or lower, or 290° C. or lower. This can improve the coatability of the resin varnish and the moldability of the resin material.

[0024] From the viewpoint of the effects of the present invention, the Mw (weight average molecular weight) of the polymer (A) is, for example, 2 × 10 3 ~1.0×10 5 , preferably 3.0 x 10 3 ~8.0×10 4 , more preferably 4.0×10 3 ~7.0×10 4 , and more preferably 5.0×10 3 ~5.0×10 4 It can be said that:

[0025] The Mw (weight average molecular weight) / Mn (number average molecular weight) of the polymer (A) can be, for example, 1.0 to 6.0, preferably 1.2 to 5.0, more preferably 1.5 to 4.0, and further preferably 1.8 to 3.0. Note that Mw / Mn is a dispersity indicating the width of the molecular weight distribution.

[0026] The weight average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (Mw / Mn) are polystyrene-equivalent values ​​obtained from a calibration curve of standard polystyrene (PS) obtained by, for example, GPC (Gel Permeation Chromatography) measurement. The measurement conditions are, for example, as follows:

[0027] Tosoh gel permeation chromatography device HLC-8320GPC Column: Tosoh TSK-GEL Supermultipore HZ-M Detector: RI detector for liquid chromatography Measurement temperature: 40℃ Solvent: THF Sample concentration: 2.0 mg / ml

[0028] The amount of low molecular weight components in polymer (A) is calculated from the ratio of the total area of ​​components with a molecular weight of 1000 or less to the total area of ​​the molecular weight distribution, based on data on molecular weight obtained, for example, by GPC measurement.

[0029] [Synthesis method of polymer (A)] The polymer (A) of this embodiment can be synthesized, for example, as follows. (Polymerization step (process S1)) First, as a monomer, for example, a predetermined norbornene-based monomer is prepared. Next, the prepared monomers are subjected to addition polymerization to obtain a polymer, for example, by coordination polymerization.

[0030] In this embodiment, the monomer and the organometallic catalyst are dissolved in a solvent, and then heated for a predetermined time to perform solution polymerization. The heating temperature can be, for example, 60° C. to 200° C., preferably 70° C. to 150° C., and more preferably 80° C. to 120° C. In this embodiment, the yield of polymer (A) can be improved by setting the heating temperature higher than that in the past.

[0031] The heating time can be, for example, 0.5 to 72 hours. It is more preferable to carry out solution polymerization after removing dissolved oxygen in the solvent by nitrogen bubbling.

[0032] In addition, a molecular weight regulator or a chain transfer agent can be used as necessary. Examples of the chain transfer agent include alkylsilane compounds such as trimethylsilane, triethylsilane, and tributylsilane. These chain transfer agents may be used alone or in combination of two or more.

[0033] Examples of the solvent used in the polymerization reaction include one or more of esters such as methyl ethyl ketone (MEK), propylene glycol monomethyl ether, diethyl ether, tetrahydrofuran (THF), toluene, ethyl acetate, and butyl acetate, and alcohols such as methyl alcohol, ethyl alcohol, and isopropyl alcohol.

[0034] The organometallic catalyst is not particularly limited as long as it allows the addition polymerization to proceed, but for example, a palladium complex or nickel complex may be coordinated with a phosphine or diimine ligand to form a counter anion, etc. One or more of these may be used.

[0035] Examples of the palladium complex include allylpalladium complexes such as (acetato-κ0)(acetonitrile)bis[tris(1-methylethyl)phosphine]palladium(I) tetrakis(2,3,4,5,6-pentafluorophenyl)borate and π-allylpalladium chloride dimer; Palladium organic carboxylates such as palladium acetate, propionate, maleate, and naphthoate; Palladium acetate triphenylphosphine complex, palladium acetate tri(m-tolyl)phosphine complex, palladium acetate tricyclohexylphosphine complex, and other palladium acetate organic carboxylic acid complexes; Palladium dibutyl phosphite, palladium p-toluenesulfonate and other organic sulfonates of palladium; β-diketone compounds of palladium such as palladium bis(acetylacetonato), palladium bis(hexafluoroacetylacetonato), palladium bis(ethylacetoacetate), and palladium bis(phenylacetoacetate); Examples of the complex include dichlorobis(triphenylphosphine)palladium, bis[tri(m-tolylphosphine)]palladium, dibromobis[tri(m-tolylphosphine)]palladium, and palladium halide complexes such as acetonyltriphenylphosphonium complexes.

[0036] Examples of the phosphine ligand include triphenylphosphine, dicyclohexylphenylphosphine, cyclohexyldiphenylphosphine, and tricyclohexylphosphine.

[0037] Examples of the counter anion include triphenylcarbenium tetrakis(pentafluorophenyl)borate, triphenylcarbenium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate, triphenylcarbenium tetrakis(2,4,6-trifluorophenyl)borate, triphenylcarbenium tetraphenylborate, tributylammonium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N,N-diethylanilinium tetrakis(pentafluorophenyl)borate, N,N-diphenylanilinium tetrakis(pentafluorophenyl)borate, and lithium tetrakis(pentafluorophenyl)borate.

[0038] The amount of the organometallic catalyst can be 300 ppm to 5000 ppm, preferably 1000 ppm to 3500 ppm, and more preferably 1500 ppm to 2500 ppm relative to the norbornene-based monomer, which can improve the yield of the polymer (A).

[0039] When the vinylnorbornene monomer, which is a raw material compound of the structural unit a represented by the general formula (1), is polymerized using the organometallic catalyst, the reaction has been difficult to proceed and the yield has been low in the past. In the present embodiment, even when the organometallic catalyst is used, the polymerization reaction of the vinylnorbornene monomer proceeds and the yield can be improved by setting the heating temperature higher than in the past as described above, and more preferably setting the amount of the organometallic catalyst within a predetermined range as described above.

[0040] (Cleaning process (process S2)) The reaction solution containing the obtained polymer is added to an alcohol such as hexane or methanol to precipitate the polymer (A). The polymer (A) is then filtered, washed with an alcohol such as hexane or methanol, and then dried. In this embodiment, for example, polymer (A) can be synthesized in this manner. According to the production method of this embodiment, the polymer (A) can be obtained in a high yield of 70% or more.

[0041] [Curing catalyst (B)] The curable resin composition for low dielectric constant material of the present embodiment may further contain a curing catalyst. As the curing catalyst, any known curing catalyst may be used as long as the effects of the present invention can be exhibited.

[0042] As the curing catalyst (B), a known curing catalyst that accelerates curing by heat or a known curing catalyst that accelerates curing by light can be used within a range in which the effects of the present invention can be exhibited. Examples of the curing catalyst (B) include a thermal acid generator, a photoacid generator, and a photoradical generator. When a certain amount of the catalyst used in the synthesis method described above remains in the polymer (A), the polymer (A) is cured by heating, and therefore a curing catalyst is not essential.

[0043] Examples of the thermal acid generator include aromatic sulfonium salts, aromatic iodonium salts, ammonium salts, aluminum chelates, boron trifluoride amine complexes, etc. One or more of these may be included as the thermal acid generator. The curable resin composition of the present embodiment may contain a thermal acid generator in an amount of preferably 1 part by mass or more and 20 parts by mass or less, and more preferably 2 parts by mass or more and 15 parts by mass or less, per 100 parts by mass of the polymer (A).

[0044] Examples of the photoacid generator include onium salt compounds, specifically cationic photopolymerization initiators such as diazonium salts, iodonium salts such as diaryliodonium salts, sulfonium salts such as triarylsulfonium salts, triarylpyrilium salts, benzylpyridinium thiocyanates, dialkylphenacylsulfonium salts, and dialkylhydroxyphenylphosphonium salts.

[0045] The curable resin composition of the present embodiment may contain a photoacid generator in an amount of preferably 1 part by mass or more and 20 parts by mass or less, and more preferably 2 parts by mass or more and 15 parts by mass or less, based on 100 parts by mass of the polymer (A). The photoacid generator and the thermal acid generator may be used in combination.

[0046] Specific examples of the photoradical generator include alkylphenone compounds such as 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropan-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, and 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone; Benzophenone compounds such as benzophenone, 4,4'-bis(dimethylamino)benzophenone, and 2-carboxybenzophenone; benzoin compounds such as benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; Thioxanthone compounds such as thioxanthone, 2-ethylthioxanthone, 2-isopropylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, and 2,4-diethylthioxanthone; halomethylated triazine compounds such as 2-(4-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-ethoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-(4-ethoxycarboxynylnaphthyl)-4,6-bis(trichloromethyl)-s-triazine; halomethylated oxadiazole compounds such as 2-trichloromethyl-5-(2'-benzofuryl)-1,3,4-oxadiazole, 2-trichloromethyl-5-[β-(2'-benzofuryl)vinyl]-1,3,4-oxadiazole, 4-oxadiazole, and 2-trichloromethyl-5-furyl-1,3,4-oxadiazole; Biimidazole compounds such as 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2,2'-bis(2,4-dichlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, and 2,2'-bis(2,4,6-trichlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole; Oxime ester compounds such as 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime); Titanocene compounds such as bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium; Benzoic acid ester compounds such as p-dimethylaminobenzoic acid and p-diethylaminobenzoic acid; acridine compounds such as 9-phenylacridine; and the like.

[0047] The curable resin composition of the present embodiment may contain a photoradical generator in an amount of preferably 1 part by mass or more and 20 parts by mass or less, and more preferably 2 parts by mass or more and 15 parts by mass or less, based on 100 parts by mass of the polymer (A).

[0048] In addition, the sensitivity and degree of crosslinking can be further improved by using a photosensitizer or a photoradical polymerization accelerator together with the photoradical generator. For example, dye compounds such as xanthene dyes and coumarin dyes, dialkylaminobenzene compounds such as ethyl 4-dimethylaminobenzoate and 2-ethylhexyl 4-dimethylaminobenzoate, and mercapto hydrogen donors such as 2-mercaptobenzothiazole and 2-mercaptobenzimidazole can be used.

[0049] (Other Ingredients) The curable resin composition of the present embodiment may contain other components, such as a filler, a resin other than the polymer (A), a crosslinking agent, an acid generator, a heat resistance improver, a developing aid, a plasticizer, a polymerization inhibitor, an ultraviolet absorber, an antioxidant, a matting agent, an antifoaming agent, a leveling agent, an antistatic agent, a dispersant, a slip agent, a surface modifier, a thixotropic agent, a thixotropic aid, a surfactant, a silane-based, aluminum-based, titanium-based or other coupling agent, a polyhydric phenol compound, and an organic solvent, depending on the purpose and required characteristics of each application.

[0050] [Curable resin composition for low dielectric constant materials] The curable resin composition for low dielectric constant material of the present embodiment can be prepared by mixing the polymer (A), the curing catalyst (B) added as necessary, and the other components described above.

[0051] The curable resin composition of the present embodiment may be a polymer solution in which a polymer is dissolved in a solvent. In this polymer solution, at least a part of the polymer may be dissolved at a liquid temperature of 25° C., but it is preferable that all of the polymer is dissolved.

[0052] Here, the solid content concentration may be the mass ratio (mass %) of the polymer dissolved in the solvent relative to 100 mass % of the resin varnish at a liquid temperature of 25° C. The content of the polymer may be expressed as the solid content concentration.

[0053] The polymer contained in the resin varnish includes a polymer (A). The content ratio of the polymer (A) in the polymer can be appropriately adjusted within a range in which heat resistance according to the application can be obtained. Specifically, the content of the polymer (A) may be, for example, 10% by mass or more, 50% by mass, 90% by mass or more, or 100% by mass, based on 100% by mass of the polymer contained in the resin varnish. As the other polymer, various copolymers may be used depending on the purpose.

[0054] The lower limit of the polymer content in the resin varnish is, for example, 5% by mass or more, preferably 7% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, based on 100% by mass of the resin varnish. On the other hand, the upper limit of the polymer content in the resin varnish is, for example, 50% by mass or less, preferably 45% by mass or less, more preferably 40% by mass or less, and even more preferably 25% by mass or less, based on 100% by mass of the resin varnish. By keeping the content within such a numerical range, the handleability of the resin varnish can be improved, and a resin material with excellent heat resistance can be realized.

[0055] The main component of the nonvolatile content in the resin varnish may be the polymer. That is, the content of the polymer is, for example, 90% by mass or more, preferably 95% by mass or more, and more preferably 100% by mass, relative to 100% by mass of the nonvolatile content. Here, the non-volatile content refers to the remainder after removing volatile components such as the solvent from the resin varnish.

[0056] It is preferable that the curable resin composition containing the polymer (A) of this embodiment is applied to a substrate, dried at 120°C for 5 minutes, and the resulting 20 µm resin film A is heated under the following conditions (1) or (2), and the remaining film ratio satisfies the following numerical value. (1) Resin film A (20 μm) is heated at 150° C. for 1 hour, and then immersed in hexane for 2 minutes. The residual film ratio calculated from the film thickness of resin film B by the following formula is 50% or more, preferably 60% or more. The upper limit is not particularly limited, but is 80% or less, preferably 70% or less. (2) Resin film A (20 μm) is heated at 180° C. for 30 minutes and then immersed in hexane for 2 minutes. The remaining film ratio calculated from the film thickness of resin film B′ by the following formula is 70% or more, preferably 80% or more. The upper limit is not particularly limited, but is 100% or less, preferably 98% or less. (formula) Residual film rate (%) = {(film thickness (μm) of resin film B (or B') immersed in hexane after heating) / (film thickness of resin film A after drying: 20 μm)} × 100

[0057] The curable resin composition for low dielectric constant material of this embodiment contains a polymer (A) obtained by polymerizing a specific norbornene-based monomer, and the resin film satisfies both the solubility characteristics (1) and (2), and therefore has excellent film-forming properties and exists in a B-stage state and a C-stage state. Therefore, as described later, it has excellent manufacturing stability for an interlayer insulating film constituting a multilayer wiring structure of a semiconductor element, a build-up layer or a core layer constituting a circuit board, and the like, and can be suitably used for these semiconductor applications. The remaining film ratio ((film thickness after immersion / film thickness before immersion)×100) of the 20 μm resin film A obtained by drying at 120° C. for 5 minutes and then immersing in hexane for 2 minutes is 0% or more and 20% or less, preferably 5% or more and 15% or less. By satisfying this remaining film ratio, the handling property of the curable resin composition for low dielectric constant material is more excellent.

[0058] [Application] The curable resin composition of the present embodiment can be cured by removing the organic solvent by drying or the like as necessary, and curing the composition by exposure to light or heat, or a combination of light and heat, to obtain a cured product.

[0059] The thermal curing can be carried out in air, in a nitrogen atmosphere, in a vacuum, etc. When the resulting cured product is required to be transparent, it is preferable to carry out the thermal curing in a nitrogen atmosphere or in a vacuum, or to use an antioxidant in combination.

[0060] The relative dielectric constant of the cured product at a frequency of 1 MHz can be preferably 2.6 or less, and more preferably 2.4 or less, which allows the cured product to be used as a low dielectric constant material. Furthermore, the dielectric tangent (tan δ) of the cured product at a frequency of 1 MHz is preferably 0.005 or less, and more preferably 0.003 or less, thereby enabling the dielectric properties of the cured product to be further improved.

[0061] This low dielectric constant material can be used in various applications, including those requiring heat resistance and use in the form of a film. The low dielectric constant material can also provide a resin film (low dielectric constant film) with excellent transparency.

[0062] Specific applications include printed circuit boards and the formation of resin films such as permanent films. The printed circuit board can be obtained by impregnating a low dielectric cloth such as a glass cloth with a curable resin composition and curing the composition. On the other hand, resin films are known as representative examples, including but not limited to, interlayer films, surface protection films, dam materials, etc. Resin films are used in electronic parts and devices such as semiconductor elements and in the manufacturing process thereof, as described below.

[0063] The interlayer film refers to an insulating film provided in a multilayer structure, and the type is not particularly limited. Examples of the interlayer film include those used in semiconductor applications such as an interlayer insulating film constituting a multilayer wiring structure of a semiconductor element, and a build-up layer or core layer constituting a circuit board. Examples of the interlayer film include those used in display element applications such as a planarizing film covering a thin-film transistor in a display device, a liquid crystal alignment film, a protrusion provided on a color filter substrate of an MVA type liquid crystal display device, or a partition wall for forming a cathode of an organic EL element.

[0064] A surface protective film refers to a film formed on the surface of an electronic component or device, or on the surface of a substrate on which these are formed, to protect the surface. Examples of such a surface protective film include a passivation film, a bump protective film or a buffer coat layer formed on a semiconductor element, or a cover coat formed on a flexible substrate, and have excellent adhesion to an underlying layer made of an organic or inorganic material. The dam material is a spacer used to form a hollow portion for arranging an optical element or the like on the substrate.

[0065] The curable resin composition of the present embodiment can be used to form such a permanent film. That is, a resin film (low dielectric constant film) made of the curable resin composition can be applied to the permanent film. The resin film (low dielectric constant film) can also be used as a part of the permanent film. For example, the curable resin composition can be applied and cured on the surface of a permanent film made of a conventionally known material, and the resin film (low dielectric constant film) can be coated on the surface.

[0066] In this embodiment, the thickness of the resin film can be appropriately adjusted depending on the application. The lower limit of the thickness of the resin film may be, for example, 10 μm or more, 15 μm or more, or 20 μm or more. On the other hand, the upper limit of the thickness of the resin film may be, for example, 100 μm or less, 70 μm or less, 60 μm or less, or 30 μm or less. By using the curable resin composition of the present embodiment, cracks do not occur even in a resin film having a thickness within the above range.

[0067] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted as long as they do not impair the effects of the present invention. EXAMPLES

[0068] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.

[0069] (Preparation of catalyst solution 1) Into a glass container that had been previously freed of moisture and was filled with a nitrogen atmosphere, 0.274 g (0.00075 mol) of allylpalladium(II) chloride (dimer), 0.403 g (0.0015 mol) of diphenylcyclohexylphosphine, and 200 g of dehydrated toluene were added and dissolved by stirring at room temperature for 1 hour. Next, 1.502 g (0.0019 mol) of N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate was added and stirred for an additional 30 minutes. The solution was then filtered through a filter under a nitrogen stream to obtain catalyst solution 1.

[0070] <Polymer synthesis> (Synthesis example 1: Copolymer 1) In a reaction vessel of appropriate size equipped with a stirrer and a cooling tube, 5-butylbicyclo[2.2.1]hept-2-ene (337.8g, 2.25mol), 5-vinylbicyclo[2.2.1]hept-2-ene (180g, 1.50mol) were dissolved in 500g of dehydrated toluene. After removing the dissolved oxygen in the system by nitrogen bubbling, the solution was stirred and when it reached 100°C, the catalyst solution 1 prepared in advance was added under a nitrogen stream. The reaction was carried out while maintaining the internal temperature at 100°C for 3 hours, and then 2g of triethylsilane was added. As a result, copolymer 1 having the following structural units was obtained. Next, the above solution was cooled to room temperature and reprecipitated using a large amount of methyl ethyl ketone, the precipitate was collected by filtration, washed with a large amount of methyl ethyl ketone, and the polymer was isolated by solid-liquid separation and dried in a vacuum dryer to obtain 373 g of a white powder polymer. The copolymer 1 thus obtained had a weight average molecular weight (Mw) of 15,000 and a polydispersity (Mw / Mn) of 2.1. [ka]

[0071] (Synthesis example 2: Copolymer 2) In a reaction vessel of appropriate size equipped with a stirrer and a cooling tube, 5-butylbicyclo[2.2.1]hept-2-ene (675.6g, 4.5mol), 5-vinylbicyclo[2.2.1]hept-2-ene (360g, 3.0mol), [bicyclo[2.2.1]hept-5-en-2-yl]triethoxysilane (70g, 0.29mol) were dissolved in 1,000g of dehydrated toluene. After removing the dissolved oxygen in the system by nitrogen bubbling, the solution was stirred and when it reached 90°C, a pre-prepared catalyst solution 1 was added under a nitrogen stream, and the reaction was carried out while maintaining the internal temperature at 90°C for 5 hours, after which 2g of triethylsilane was added. As a result, a copolymer 2 having the following structural units was obtained. Next, the above solution was cooled to room temperature and reprecipitated using a large amount of methyl ethyl ketone, the precipitate was collected by filtration, washed with a large amount of methyl ethyl ketone, and the polymer was isolated by solid-liquid separation and dried in a vacuum dryer to obtain 890 g of a white powder polymer. The copolymer 2 thus obtained had a weight average molecular weight (Mw) of 24,000 and a polydispersity (Mw / Mn) of 2.5. [ka]

[0072] (Comparative Synthesis Example 1: Homopolymer 1) In a reaction vessel of suitable size equipped with a stirrer and a cooling tube, 5-butylbicyclo[2.2.1]hept-2-ene (2,252 g, 15.0 mol) and triethylsilane (1.0 g, 0.009 mol) were weighed and dissolved in 8,000 g of dehydrated toluene. After removing the dissolved oxygen in the system by nitrogen bubbling, the solution was stirred and when it reached 60°C, a pre-prepared catalyst solution 1 was added under a nitrogen stream, and the reaction was carried out while maintaining the internal temperature at 60°C for 4 hours, and then 2 g of triethylsilane was added. This resulted in homopolymer 1 having the following structural units. Next, the above solution was cooled to room temperature and reprecipitated using a large amount of methyl ethyl ketone, and the precipitate was filtered off, the filtered product was washed with a large amount of methyl ethyl ketone, and the homopolymer was taken out by solid-liquid separation and dried in a vacuum dryer to obtain 1,800 g of white powder homopolymer. The homopolymer 1 thus obtained had a weight average molecular weight (Mw) of 450,000 and a polydispersity (Mw / Mn) of 4.2. [ka]

[0073] (Comparative Synthesis Example 2: Homopolymer 2) 5-vinylbicyclo[2.2.1]hept-2-ene (500g, 4.17mol) was weighed and dissolved in 500g of dehydrated toluene in a suitable size reaction vessel equipped with a stirrer and a cooling tube. After removing dissolved oxygen in the system by nitrogen bubbling, the solution was stirred and when it reached 100°C, a pre-prepared catalyst solution 1 was added under a nitrogen stream, and the reaction was carried out while maintaining the internal temperature at 100°C for 8 hours, and then 2g of triethylsilane was added. This resulted in homopolymer 2 having the following structural units. Next, the above solution was cooled to room temperature and reprecipitated using a large amount of methyl ethyl ketone, and the precipitate was filtered off, the filtered product was washed with a large amount of methyl ethyl ketone, and the homopolymer was taken out by solid-liquid separation and dried in a vacuum dryer to obtain 280g of white powder homopolymer. The homopolymer 2 thus obtained had a weight average molecular weight (Mw) of 7,000 and a polydispersity (Mw / Mn) of 2.2. [ka]

[0074] The weight average molecular weight (Mw) and number average molecular weight (Mn) of the obtained polymer were determined using polystyrene equivalent values ​​obtained from a calibration curve of standard polystyrene (PS) obtained by GPC measurement. The measurement conditions were as follows: Tosoh Corporation gel permeation chromatography device HLC-8320GPC Column: TSK-GEL Supermultipore HZ-M manufactured by Tosoh Corporation Detector: RI detector for liquid chromatography Measurement temperature: 40℃ Solvent: THF Sample concentration: 2.0 mg / ml

[0075] <Resin composition> Film forming properties Example 1 4 g of Copolymer 1 obtained in Synthesis Example 1 was dissolved in 6 g of toluene to prepare a resin solution. The polymer was completely dissolved, and a film was formed on a silicon wafer using a spin coater and dried at 120° C. for 5 minutes to obtain a 20 μm resin film. The obtained resin film was heated at 150°C for 1 hour in a nitrogen atmosphere and then cooled to room temperature. When the resin film was immersed in hexane, the remaining film ratio calculated by the following formula was 58%. In addition, the dried 20 μm resin film was heated in a nitrogen atmosphere at 180° C. for 30 minutes and then returned to room temperature. When the resin film was immersed in hexane, the remaining film ratio calculated by the following formula was 84%. (formula) Residual film rate (%) = {(Thickness of resin film immersed in hexane after heating (μm)) / (Thickness of resin film after drying: 20 μm)} × 100

[0076] Example 2 4 g of Copolymer 2 obtained in Synthesis Example 2 was dissolved in 6 g of toluene to prepare a resin solution. The polymer was completely dissolved, and a film was formed on a silicon wafer using a spin coater and dried at 120° C. for 5 minutes to obtain a 20 μm resin film. The obtained resin film was heated at 150°C for 1 hour in a nitrogen atmosphere and then cooled to room temperature. When the resin film was immersed in hexane, the residual film ratio calculated by the above formula was 63%. In addition, the 20 μm resin film after drying was heated in a nitrogen atmosphere at 180° C. for 30 minutes and then returned to room temperature. When the resin film was immersed in hexane, the residual film ratio calculated by the above formula was 94%.

[0077] Comparative Example 1 2 g of the homopolymer 1 obtained in Comparative Synthesis Example 1 was dissolved in 8 g of toluene to prepare a resin solution. The polymer was completely dissolved, and a film was formed on a silicon wafer using a spin coater and dried at 120° C. for 5 minutes to obtain a 20 μm resin film. The obtained resin film was heated at 150°C for 1 hour in a nitrogen atmosphere and then cooled to room temperature. When the resin film was immersed in hexane, the residual film rate calculated by the above formula was 0%.

[0078] Comparative Example 2 4 g of homopolymer 2 obtained in Comparative Synthesis Example 2 was dissolved in 6 g of toluene to prepare a resin solution. The polymer was completely dissolved, and a film was formed on a silicon wafer using a spin coater. The film was dried at 120°C for 5 minutes to obtain a 10 μm resin film. However, cracks were present and film formation was difficult.

[0079] <1MHz dielectric constant measurement> The polymer was applied to a 4-inch silicon wafer using a spin coater to form a film, which was then dried at 120° C. for 10 minutes and heated in a vacuum at 180° C. for 30 minutes to form a 2.0 μm thick film. The test equipment used was an Agilent Technologies HP-4284A, and the parallel capacitance Cp and conductance G were measured at a measurement frequency of 1 MHz. The relative dielectric constant and dielectric tangent were calculated and the results are shown in Table 1 below.

[0080] <Transparency assessment> The polymer was formed on a PET film, vacuum dried at 100°C for 60 minutes, peeled off from the PET film, and heated at 180°C for 30 minutes under vacuum to obtain a 50μm film. The total light measurement efficiency of the obtained film was measured based on JIS-K-7361.

[0081] [Table 1]

[0082] It has been revealed that the curable resin composition for low dielectric constant materials of the present invention, which contains a polymer including a structural unit represented by the general formula (1) and a structural unit represented by the general formula (2), can give a transparent cured product with excellent low dielectric properties, as shown in Table 1. Furthermore, it has been revealed that the curable resin composition for low dielectric constant materials of the present invention has excellent film-forming properties and exists in a B-stage state and a C-stage state, and therefore has excellent manufacturing stability for an interlayer insulating film constituting a multilayer wiring structure of a semiconductor element, a build-up layer or core layer constituting a circuit board, and the like, and is suitable for use in such semiconductor applications.

Claims

1. A curable resin composition for low dielectric constant material, comprising a polymer including at least one structural unit a represented by the following general formula (1), at least one structural unit b represented by the following general formula (2), and at least one structural unit c represented by the following general formula (3): 【Chemistry 1】 (In general formula (1), m is 0, 1 or 2. In the general formula (2), X represents a linear or branched alkyl group having 3 to 20 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, or an aryl group. In the general formula (3), R each independently represents an alkoxy group having 1 to 3 carbon atoms or an alkyl group having 1 to 3 carbon atoms, and at least two R are alkoxy groups having 1 to 3 carbon atoms. l is 0, 1, or 2. p is an integer of 0 to 3.

2. 2. The curable resin composition for low dielectric constant materials according to claim 1, wherein the polymer does not contain a polar functional group selected from a carboxyl group, an epoxy group, an ester group, and an amino group.

3. The curable resin composition for low dielectric constant materials according to claim 1 or 2, wherein the polymer does not contain a constitutional unit derived from maleic acid or maleimide.

4. The curable resin composition for low dielectric constant materials according to any one of claims 1 to 3, further comprising a curing catalyst.

5. The curable resin composition for a low dielectric constant material according to claim 4 , wherein the curing catalyst is a photoacid generator or a photoradical generator.

6. The curable resin composition for low dielectric constant materials was applied and dried at 120° C. for 5 minutes to obtain a 20 μm resin film A. The residual film ratio calculated from the film thickness of resin film B after heating at 150° C. for 1 hour and then immersing in hexane for 2 minutes using the following formula is 50% or more, The residual film ratio calculated from the film thickness of the resin film B' after heating at 180° C. for 30 minutes and then immersing in hexane for 2 minutes using the following formula is 70% or more. The curable resin composition for low dielectric constant materials according to any one of claims 1 to 5. (formula) Residual film rate (%)={(film thickness (μm) of resin film B (or B′) immersed in hexane after heating) / (film thickness of resin film A after drying: 20 μm)}×100

7. A cured product obtained by curing the curable resin composition for low dielectric constant materials according to any one of claims 1 to 6.

8. The cured product according to claim 7, having a relative dielectric constant of 2.6 or less and a dielectric loss tangent (tan δ) of 0.005 or less at a frequency of 1 MHz.

9. A resin film comprising the cured product according to claim 7 or 8 and having a thickness of 10 μm or more.

10. A low dielectric constant material comprising the cured product according to claim 7 or 8.

Citation Information

Patent Citations

  • Cyclic olefin-based (Co)Polymer and optical material

    JP2002012624A

  • Crosslinked polymer

    JP2010254880A

  • Resin composition

    JP2013231171A

  • Cyclic olefin copolymer composition and cross-linked body of the same

    JP2015193680A

  • Cyclic olefin copolymer and method for producing same

    JP2019504170A